Elevated MS4A12 expression is indicative of resistance to concurrent chemoradiotherapy and inferior survival in patients with rectal cancer - Chih-I Chen; Yi-Kai Kao; Po-Wen Yang; Pin-Chun Chen; Ching-Chieh Yang; Wan-Shan Li; Hsin-Hwa Tsai; Yu-Jen Wang; Hong-Yue Lai (Radiation Oncology)
Abstract Introduction In individuals presenting with locally advanced rectal cancer, the therapeutic strategy of neoadjuvant concurrent chemoradiotherapy (CCRT) aims to enhance tumor downstaging; however, only a subset of patients exhibit a favorable response. Molecular stratification, combined with the traditional tumor staging system (TNM), is a promising approach for predicting treatment efficacy and patient outcomes. Therefore, we intend to better grasp the molecular basis of CCRT resistance and guide therapeutic strategies with greater precision. Methods We utilized a public rectal cancer transcriptomic dataset (n = 46) to predict responsiveness to neoadjuvant CCRT by analyzing signal transduction-related genes. In our well-characterized rectal cancer cohort (n = 343), we assessed correlations between membrane-spanning 4-domains A12 (MS4A12) immunostaining and clinicopathological characteristics using Pearson’s chi-squared test. To calculate survival rates, we employed the Kaplan–Meier method with a log-rank test. Additionally, we conducted multivariate analyses with the Cox proportional hazards model to identify independent prognostic biomarkers. Results We identified that the MS4A12 gene is highly expressed in rectal cancer resistant to CCRT. Elevated MS4A12 expression, confirmed by immunohistochemical staining, is significantly associated with advanced tumor status after CCRT (p < 0.001), positive node status both before and after CCRT (p = 0.01 and p = 0.004), the presence of perineural and vascular invasion (p = 0.006 and p = 0.001), and low or no response to CCRT (p < 0.001). Notably, high MS4A12 immunoexpression is strongly correlated with reduced patient survival in rectal cancer. Mechanically, high MS4A12 expression is significantly associated with aberrant glycosylation and B-cell infiltration. Conclusion MS4A12 expression may offer a helpful predictive and prognostic indicator for identifying patients who could gain advantages from neoadjuvant CCRT.